Exploring Students’ Teaching Experiences through the PMS-MBKM Program: Teaching at School-Emancipated Learning Emancipated Campus - Selfiani; Sartin T. Miolo; Titien Fatmawaty Mohammad (Kirana Publisher (KNPub), 2026)
This study is aim to find out the students’ teaching experience through the PMS-MBKM program (teaching at school-emancipated learning emancipated campus) in teaching activities, technology adaptation activities, and school administration activities. This research employed a qualitative method with phenomenology approach that consists of 6 participants of English Education Study Program, Universitas Negeri Gorontalo, who participated in the first batch of the PMS-MBKM program in 2022. The data collected through semi-structured interviews with interactive model analysis. The findings showed that several themes from the interview. They were the experiences to teaching activities, technology adaptation activities, and school administration activities. This research is expected to be useful for knowing the extent of the students’ development during the Teaching Campus program. In addition, this research can be used as a reference for the implementation of the next PMS-MBKM program.